2013
DOI: 10.1002/jgrd.50324
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fresh and aged biomass burning events using multiwavelength Raman lidar and mass spectrometry

Abstract: [1] This paper focuses on optical and microphysical properties of long-range transported biomass burning (BB) aerosols and their variation with atmospheric evolution (ageing), as observed by a multiwavelength Raman lidar, part of EARLINET (European Aerosol LIdar NETwork). Chemical analysis of the atmospheric aerosol was done using a colocated aerosol mass spectrometer (AMS). One relevant optical parameter for the ageing process is the Ångström exponent. In our study, we find that it decreases from 2 for fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 69 publications
21
104
0
Order By: Relevance
“…The lidar ratios of biomass burning aerosols are among the highest compared to the literature, with a mean value of 92 ± 10 sr (e.g. Müller et al, 2007;Nicolae et al, 2013;Amiridis et al, 2009). Urban/industrial aerosol layers were found to have lower lidar ratio values in the range between 41 and 59 sr at 355 nm.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The lidar ratios of biomass burning aerosols are among the highest compared to the literature, with a mean value of 92 ± 10 sr (e.g. Müller et al, 2007;Nicolae et al, 2013;Amiridis et al, 2009). Urban/industrial aerosol layers were found to have lower lidar ratio values in the range between 41 and 59 sr at 355 nm.…”
Section: Resultsmentioning
confidence: 87%
“…found larger biomass burning aerosols with an effective radius of approximately 0.25 µm. Effective radii in the range between 0.19 and 0.44 µm were found for biomass burning aerosol layers resulting from long-range transport across Romania (Nicolae et al, 2013). Müller et al (2007) presented values ranging between 0.13 and 0.15 nm for plumes ageing between 1 and 3 days.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In all other cases, the lidar ratio is similar, ranging from 59 to 61 sr. Differences with the summer levels could be attributed to different aerosol transportation paths and thus either more mixing with continental particles or different aging of smoke (e.g., Amiridis et al, 2009;Nicolae et al, 2013;Papayannis et al, 2014). The BAE values are available only for summer and autumn, ranging from 1.3 to 1.4.…”
Section: Biomass Burning Mixturesmentioning
confidence: 99%
“…In particular, EARLINET data have been recently used for aerosol characterization in terms of optical and microphysical properties in conjunction with in situ measurements and transport models (e.g. [9], [10], [11], [12]). …”
Section: The Lidar Calibration Training Laboratorymentioning
confidence: 99%